Prognosis Between ST-Elevation and Non-ST-elevation Myocardial Infarction in Older Adult Patients - Chang, Shih-Sheng; Lu, Chiung-Ray; Chen, Ke-Wei; Kuo, Zhe-Wei; Yu, Shao-Hua; Lin, Shih-Yi; Shi, Hong-Mo; Yip, Hei-Tung; Kao, Chia-Hung (Frontiers in Cardiovascular Medicine, 2022)
Background: Whether there is a difference in prognosis between elderly patients with ST-elevation myocardial infarction (STEMI) and non-ST-elevation myocardial infarction (NSTEMI) remains mysterious. Methods: We conducted a retrospective cohort study by analyzing the data in the Longitudinal Health Insurance Database (LHID) in Taiwan to explore differences between STEMI and NSTEMI with respect to in-hospital and long-term (3-year) outcomes among older adult patients (aged ≥65 years). Patients were further stratified based on whether they received coronary revascularization. Results: In total, 5,902 patients aged ≥65 years with acute myocardial infarction (AMI) who underwent revascularization (2,254) or medical therapy alone (3,648) were included. In the revascularized group, no difference was observed in cardiovascular (CV) and all-cause mortality during hospitalization or at 3-year follow-up between the two AMIs. Conversely, in the non-revascularized group, patients with NSTEMI had higher crude odds ratio (cOR) for all-cause death during hospitalization [cOR: 1.33, 95% confidence interval (CI) = 1.07–1.65] and at 3-year follow-up (cOR: 1.47, 95% CI = 1.21–1.91) relative to patients with STEMI. However, after multivariable adjustments, only NSTEMI indicated fewer in-hospital CV death [adjusted odds ratio (aOR): 0.75, 95% CI = 0.58–0.98] than STEMI in non-revascularized group. Moreover, major bleeding was not different between patients with STEMI or NSTEMI aged ≥65 years old. Conclusion: Classification of AMI is not associated with the difference of in-hospital or 3-year CV and all-cause death in older adult patients received revascularization. In a 3-year follow-up period, STEMI was an independent predictor of a higher incidence of revascularization after the index event. Non-ST-elevation myocardial infarction had more incidence of MACE than patients with STEMI did in both treatment groups.